ANALYSIS OF THE ROLE AND CHALLENGES OF PARENTS IN EDUCATING CHILDREN POST-PANDEMIC COVID-19 - Bahari, Arman Adiviani (PT Altin Riset Publishing, 2023)
The aim of this research is to analyze the role and challenges of parents in educating children after the Covid-19 pandemic. The research method used by researchers is through qualitative methods, researchers analyze the role of parents in educating children based on a developmental psychology perspective. The research results show that authoritative parenting tends to be more effective in preventing children's bad habits in playing with gadgets by encouraging children to always be active in positive activities, in this case parents act as managers and initiators for children. The challenges faced by parents in the child's education process are that the child's volitional and emotional functions are not yet fully functioning properly, so parents are required to be more patient and provide gentle treatment towards children.